Repurposing of epalrestat for neuroprotection in parkinson’s disease via activation of the KEAP1/Nrf2 pathway - Huafang Jia; Mengru Liu; Hong Jiang; Zhen Qiao; Kaiyue Ren; Xixun Du; Xi Chen; Qian Jiao; Fengyuan Che (Journal of Neuroinflammation)
Abstract Background Epalrestat (EPS), an aldose reductase inhibitor, is used to alleviate peripheral nerve disorder of diabetic patients in clinical therapy. Even though EPS exerted effects in central nervous system diseases, the neuroprotection and underlying molecular mechanism in neurodegenerative diseases, especially Parkinson’s disease (PD), remains obscure. Our study aimed to investigate the potential of EPS suppressed PD progression both in vivo and in vitro. Methods We used 1-methyl-4-phenylpyridillium ion (MPP+)-treated PD cells and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated PD mice to investigate the protective function and molecular mechanism of EPS in PD. EPS was administered three times daily through oral route 3 days before model establishment for 5 consecutive days. Behavioral manifestation of mice was conducted using open field test, rotarod test and CatWalk gait analysis. Immunofluorescence was used to detect dopaminergic (DAergic) neurons survival in the substantia nigra. Subsequently, oxidative stress, mitochondrial function and KEAP1/Nrf2 signaling pathway in PD models were detected through molecular biology methods to assess the effect and downstream mechanisms of EPS on PD. Molecular docking, surface plasmon resonance and cellular thermal shift assay were used to verify the direct binding of EPS and KEAP1. Results We found that EPS exhibited potent antiparkinsonian activity in PD models both in vivo and in vitro. PD models treated with EPS manifested alleviated oxidative stress and mitochondrial dysfunction. Furthermore, we found EPS activated the Nrf2 signaling pathway which contributed to DAergic neurons survival in PD models. Particularly, we firstly confirmed that EPS competitively binds to KEAP1 and enhanced its degradation, thereby activating the Nrf2 signaling pathway. Conclusions Collectively, EPS attenuates oxidative stress and mitochondrial dysfunction by directly binding KEAP1 to activate the KEAP1/Nrf2 signaling pathway, further reducing DAergic neurons damage. These findings suggest that EPS has great potential to become a therapeutic for PD as a clinically effective and safe medicine.